2008
DOI: 10.1590/s0004-282x2008000600012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NMDA and non-NMDA antagonists on acute and inflammatory pain in the trigeminal territory: a placebo control study

Abstract: -NMDA and non-NMDA receptors are involved in spinal transmission of nociceptive information in physiological and pathological conditions. Our objective was to study the influence of NMDA and non-NMDA receptor antagonists on pain control in the trigeminal system using a formalin-induced orofacial pain model. Motor performance was also evaluated. Male Rattus norvegicus were pre-treated with topiramate (T) (n=8), memantine (M) (n=8), divalproex (D) (n=8) or isotonic saline solution (ISS) (n=10) intraperitoneally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Currently, reported mechanisms describing the pain include release of inflammatory mediators and neuropeptides [1], [2], aberrant expression of pain-relevant genes [3], [4] and peripheral and central sensitization [5], [6], ect. The trigeminal ganglion (TG) is a crucial site for pain transmission and pain modulation from the peripheral to central nerve system in oral maxillofacial region [7].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, reported mechanisms describing the pain include release of inflammatory mediators and neuropeptides [1], [2], aberrant expression of pain-relevant genes [3], [4] and peripheral and central sensitization [5], [6], ect. The trigeminal ganglion (TG) is a crucial site for pain transmission and pain modulation from the peripheral to central nerve system in oral maxillofacial region [7].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence indicates that trigeminal neuralgia and facial nerve palsy frequently occur in ACC cases (5,6,21,25). Several studies have suggested the involvement of an inflammatory reaction in neuropathic pain and perineural invasion (28,29). Moreover, it should be noted that perineural invasion of adnexal carcinoma has been shown to be implicated in local edema and paresthesia (30).…”
Section: Discussionmentioning
confidence: 99%
“…A few experimental research studies on headache were developed in Brazil . We had introduced a new experimental model of headache using rats injected with formalin in the frontal area, and the behavioral changes induced by the provoked pain were observed .…”
Section: Publications In Headache Medicinementioning
confidence: 99%
“…[207][208][209]386,387,390,402,404,406,412 A few experimental research studies on headache were developed in Brazil. 252,461 We had introduced a new experimental model of headache using rats injected with formalin in the frontal area, and the behavioral changes induced by the provoked pain were observed. 54,86 The behavior related to the pain felt in the head consisted of two phases, and the response was reduced by previous treatment with aspirin.…”
Section: Publications In Headache Medicinementioning
confidence: 99%